What Drives Online Buyers? Insights from Product Quality, Price Perception, and Marketing Communication in Calendar Purchases - Halim, Steven; Hermeindito (Manunggal Halim Jaya, 2026)
This research aims to analyze the influence of product quality, price perception, and marketing communication on purchase decisions for Soyami Stuff calendars in e-commerce, conducted in Indonesia. A quantitative approach was used by distributing questionnaires to 100 respondents, selected using purposive sampling from a population of 4,943 online buyers who had previously purchased calendars from the Soyami Stuff store on e-commerce platforms. The sample size was determined using Slovin's formula with a 10% margin of error. The data were analyzed using multiple linear regression. In this research, the independent variables used are product quality (X1), price perception (X2), and marketing communication (X3), while the dependent variable was purchase decisions (Y). Based on the multiple linear regression analysis, marketing communication had the strongest influence on purchase decisions with a standardized coefficient (β) of 0.438 and a significance level (p) of 0.006. Price perception had a standardized coefficient of 0.306 (p = 0.041), while product quality had a coefficient of 0.274 (p = 0.003). The regression model was statistically significant overall, with an F-value of 15.832 and a significance level of p < 0.001. The coefficient of determination (R²) was 0.331, indicating that 33.1% of the variance in consumer purchase decisions could be explained by the three independent variables.